Multicultural Education Design Through Crafts Learning Wood on Students PGSD UAD - Fery Setyaningrum; Sagaf Adzkia; Indah Wenerda (Universitas Negeri Malang, 2024)
The Indonesian nation must become more aware of cultural diversity, as many students still lack this awareness. Indonesia is known for its multicultural and pluralistic society, emphasizing the need to introduce cultural diversity in education. At PGSD UAD, fine arts and skills classes, particularly woodcraft, embody multicultural education principles. Understanding cultural pluralism helps maintain cultural heritage and mutual respect. This research aims to describe the woodcraft learning process at PGSD UAD and design multicultural education through this medium. Using qualitative methods like observation, interviews, and document reviews, the study focuses on UAD PGSD students practicing wooden batik in Krebet Village. The findings reveal a structured learning process involving material selection, design stages, and creating batik motifs representing diverse cultures. Multicultural education at PGSD UAD fosters an inclusive environment where students access equal educational opportunities, regardless of race, ethnicity, or other factors. Woodcraft products reflect various ethnic influences from across Indonesia.